2018
DOI: 10.1093/jee/toy006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polygonum persicaria (Polygonales: Polygonaceae) Extracted Agglutinin on Life Table and Antioxidant Responses in Helicoverpa armigera (Lepidoptera: Noctuidae) Larvae

Abstract: Plant lectins could reduce insect populations by imposing imbalances in biology and physiology. Here, an agglutinin was extracted from Polygonum persicaria L. (PPA; Polygonales: Polygonaceae) and its effects were investigated on life table parameters and antioxidant system of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae). PPA significantly changed demographic parameters showing adverse effects on age-stage survival rate (Sxj), age-specific survival rate (lx), age-specific fecundity rate (mx), age stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Colonies with inserts were screened with blue/white X-gal selection under standard ampicillin conditions. Plasmid DNA was extracted from recombinant bacterial cells using the alkaline lysis method described by Sambrook and Russell [37], and the DNA was sequenced from multiple [5][6][7][8][9][10] different independent bacterial colonies by Bioneer (Daejeon, Korea). Table 1.…”
Section: Hsp Gene Cloningmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonies with inserts were screened with blue/white X-gal selection under standard ampicillin conditions. Plasmid DNA was extracted from recombinant bacterial cells using the alkaline lysis method described by Sambrook and Russell [37], and the DNA was sequenced from multiple [5][6][7][8][9][10] different independent bacterial colonies by Bioneer (Daejeon, Korea). Table 1.…”
Section: Hsp Gene Cloningmentioning
confidence: 99%
“…The antioxidant system is well-regulated, controlling ROS levels during normal metabolism, but also capable of increasing enzyme activities and antioxidants during various stresses. Induction of the antioxidant system has been observed in many insects subjected to different stresses, such temperature [2; 4; 5; 6], dietary oxidants [7], pesticide exposures [8; 9], oxygen deprivation [10] and infections or parasitisms [11; 12].…”
Section: Introductionmentioning
confidence: 99%
“…Helicoverpa armigera (Hübner) is recognized as a polyphagous and cosmopolitan insect pest and has a high damage potential for various economically important crops around the world, including cotton, corn, tomatoes, sorghum, soybeans, and tobacco [ 1 ]. Some biological characteristics, such as polyphagy, mobility, fecundity, and facultative diapauses, can increase the survival and population outbreaks of the pest in agroecosystems [ 2 ]. These pests, which attack more than 150 different host species, are considered as the most economically important insect pests in many countries, such as India, Japan, China, and Southeast Asia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ramzi, Sahragard, and Zibaee () reported that Citrullus colocynthis agglutinin significantly reduced ecological performance of Ectomyelois ceratoniae Zeller (Lepidoptera: Pyralidae) through discrepancies in intermediary metabolism of larvae. Rahimi, Hajizadeh, Zibaee, and Jalali Sendi (a, b) demonstrated that Polygonum persicaria lectin not only reduced nutritional performance and life table parameters but also induced antioxidative stress in Helicoverpa armigera Hübner (Lepidoptera: Noctuidae).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, entomotoxic effects of Polygonum persicaria agglutinin (PPA) were determined on life table parameters, nutrition and antioxidant responses of H. armigera (Rahimi et al, ; Rahimi, Hajizadeh, Zibaee, & Jalali Sendi, ). Since there is no report on the effects of plant lectins on immune systems of insect, the current study was designed to explore this potentiality in PPA on the numbers of hemocytes, phenoloxidase activity, and expression of some genes involved in immune responses.…”
Section: Introductionmentioning
confidence: 99%